A Node Deployment Strategy Considering Environmental Factors and the Number of Nodes in Surveillance and Reconnaissance Sensor Networks. (14th August 2012) - Kim, Yonghyun; Yeo, Myungho; Kim, Daesik; Chung, Kwangsue
Abstract : In wireless sensor networks, sensor coverage and network connectivity problems are caused by the restricted sensing and communication range of the nodes. To solve these problems, many studies have been undertaken but most of this work is too limited to be applied to real environments because they do not consider various environmental factors that affect wireless sensor network deployment. In this paper, we propose a node deployment strategy that considers environmental factors and the number of nodes for surveillance and reconnaissance sensor networks (SRSNs). Our strategy consists of four steps for the installation of a surveillance and reconnaissance sensor network: the analysis of environmental factors, sensor node deployment, selection of monitoring sites and relay node deployment. It deploys the sensor nodes, and relay nodes while considering features of the surveillance and reconnaissance sensor networks as well as environmental factors. Simulation results show that our strategy improves sensor coverage and network connectivity.